TINJAUAN YURIDIS TERHADAP KAWIN KONTRAK DALAM PERSPEKTIF HUKUM PERJANJIAN DAN HUKUM ISLAM - Mutiara Citra; Rika Lestari; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The phenomenon of marriage contract in Indonesia begins with the existence of an agreement between both parties on the duration of marriage, dowry price, rights and obligation as weel as anything else deemed necessary by the person. The contract is contrary to the legitimate requirements of article 1320 Kitab Undang-Undang Hukum Perdata, agreement that objective conditions relating to the lawful cause and a certain thing. Agreement is null and void if no eligible objective contract.Isamic law at first to justify the practice of temporary marriages, but due to more negative sessions, then Allah SWT forbids marriage contract until the day end. This is evidenced by the hadith narrated by Muslim. However, althougt it has been in unlawful and prohibited, in fact temporary marriages still occur in some areas in Indonesia, as peak area of Bogor, Jepaa, and Singkawang.Key Words : Marriage Contract – Agreement – Islamic Law.